Revised surveillance case definitions: poliovirus (non-paralytic) infection; poliovirus (paralytic) infection; viral haemorrhagic fever - Case Definitions Working Group (Communicable Diseases Intelligence, 2013)
Disclaimer: The views expressed in this item are those of the individual authors, and do not necessarily represent the views of the Communicable Diseases Intelligence journal or the Australian Centre for Disease Control. While this Policy and Guidelines item was drafted with consideration to the then-available information on the condition(s) addressed within, it may not be complete and may not represent the currently understood best practice for the referenced condition(s). Readers are advised to refer to the most recent guidance on this matter, where such guidance exists and where its authoritativeness can be established. These guidelines do not replace the need for clinical judgment to be exercised for each individual circumstance, nor the necessity for expert advice to be obtained as appropriate. This report provides the revised Surveillance case definitions approved by the Communicable Diseases Network Australia (CDNA) since 1 July 2013. The Case Definitions Working Group (CDWG) is a subcommittee of the CDNA and comprises members representing all states and territories, the Australian Government Department of Health (DoH), the Public Health Laboratory Network (PHLN), OzFoodNet, the Kirby Institute, the National Centre for Immunisation Research and Surveillance (NCIRS) and other communicable disease experts. CDWG develops and revises surveillance case definitions for all diseases reported to the National Notifiable Diseases Surveillance System. Surveillance (NNDSS) case definitions incorporate laboratory, clinical and epidemiological elements as appropriate. These case definitions will be implemented on 1 January 2014 and supersede any previous versions.